2022
DOI: 10.1007/s00062-022-01213-7
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Characteristics of Damage Along Fiber Tracts in Patients with Type 2 Diabetes Mellitus

Abstract: Purpose The white matter (WM) of the brain of type 2 diabetes mellitus (T2DM) patients is susceptible to neurodegenerative processes, but the specific types and positions of microstructural lesions along the fiber tracts remain unclear. Methods In this study 61 T2DM patients and 61 healthy controls were recruited and underwent diffusion spectrum imaging (DSI). The results were reconstructed with diffusion tensor imaging (DTI) and neurite orientation disper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 70 publications
1
7
0
Order By: Relevance
“…In our study, compared with HCs, T2DM patients showed an extensive increase in the mean MD, AD, and RD values of association fibers and CF. Specifically, the MD values of CF_Major, CF_Minor, right IFOF, and right ILF increased, consistent with previous studies 32 , 41 , 42 increased. In the node-wise comparison, the nodes 11–16 of MD in right IFOF in T2DM patients were increased.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, compared with HCs, T2DM patients showed an extensive increase in the mean MD, AD, and RD values of association fibers and CF. Specifically, the MD values of CF_Major, CF_Minor, right IFOF, and right ILF increased, consistent with previous studies 32 , 41 , 42 increased. In the node-wise comparison, the nodes 11–16 of MD in right IFOF in T2DM patients were increased.…”
Section: Discussionsupporting
confidence: 91%
“…The calculation was done based on two-tailed test, α of 0.05, and power of 0.8, the ratio of sample size between T2DM group and HC group was 1:1. Referring to previous studies 15 , 32 34 , the diffusion metrics values of bilateral IFOF, CF_Major, CF_Minor were used as the main observation indicators. The data of our preliminary experiment were used for sample size calculation.…”
Section: Methodsmentioning
confidence: 99%
“…Consistently, in first-episode psychosis and antipsychotic naïve patients, a potential association of insulin resistance with diminished response to antipsychotic treatment can be identified [8]. Further, abnormal neuroimaging findings have been detected in diabetic and pre-diabetic patients without psychiatric illness [177][178][179]. Thus, greater attention should be paid to different patterns of brain functional and structural connectivity in psychotic patients detected in the absence or presence of metabolic abnormalities, with further implications for treatment responsiveness and resistance.…”
Section: Limitationsmentioning
confidence: 93%
“…Neuroimaging studies have recently highlighted the association between insulin resistance and abnormal brain structure and function in individuals with T2DM [11][12][13][14]. One study revealed a link between lower gray matter density in frontotemporal regions and the homeostatic model assessment of insulin resistance (HOMA-IR) [11].…”
Section: Introductionmentioning
confidence: 99%
“…One study revealed a link between lower gray matter density in frontotemporal regions and the homeostatic model assessment of insulin resistance (HOMA-IR) [11]. An automatic fiber quantification study also demonstrated a positive correlation between insulin resistance and aberrant orientation dispersion index in the right arcuate fasciculus [12]. Functional magnetic resonance imaging (MRI) studies further supported the connection between the abnormal brain connectivity patterns and HOMA-IR in T2DM [13, 14].…”
Section: Introductionmentioning
confidence: 99%